Flow and heat transfer profiles in a heat exchanger tube equipped with X-V baffles (XVB): A numerical analysis - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2023)
Simulations of laminar air flow and thermal configurations through a heat exchanger tube (HXT) equipped with X-V baffles (XVB) are performed. The Reynolds number is between 100 – 2000. The current numerical problem is solved by a numerical method (the finite volume analysis). Effects of the XVB sizes, the XVB distances and the flow directions on the flow and thermal profiles are discussed. The XVB size (b/D) is set between 0.05 – 0.20 and the XVB distance (P/D) is set to 1, 1.5 and 2. X-axis is the flow axis. The positive and negative x-axis are investigated. Two baffle configurations (Type I and II) are compared. The streamlines, vortex flows, temperature profiles and Nusselt number profiles in the HXT installed with these two XVB configurations (Type I and II) are described. The variations for the friction factor ratio (f/f0), Nusselt number ratio (Nu/Nu0) and thermal enhancement factor (TEF) within the HXT equipped with the XVB are presented. In addition, the TEF of 4.07 is found to be the best value for the present investigation.
Keywords: Baffle; Heat Transfer Mechanisms